2011
DOI: 10.1016/j.neuron.2010.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Variance as a Signature of Neural Computations during Decision Making

Abstract: Traditionally, insights into neural computation have been furnished by averaged firing rates from many stimulus repetitions or trials. We pursue an analysis of neural response variance to unveil neural computations that cannot be discerned from measures of average firing rate. We analyzed single-neuron recordings from the lateral intraparietal area (LIP), during a perceptual decision-making task. Spike count variance was divided into two components using the law of total variance for doubly stochastic processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
374
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(424 citation statements)
references
References 47 publications
36
374
2
2
Order By: Relevance
“…When gain is higher, a stimulus is encoded with higher precision (11,12). Variability in gain across items and trials is consistent with observations of single-neuron firing rate variability (13)(14)(15) and attentional fluctuations (16,17).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…When gain is higher, a stimulus is encoded with higher precision (11,12). Variability in gain across items and trials is consistent with observations of single-neuron firing rate variability (13)(14)(15) and attentional fluctuations (16,17).…”
supporting
confidence: 85%
“…Supporting this notion, doubly stochastic processes can well describe spike counts in lateral intraparietal cortex (LIP) (13), visual cortex (15), and other areas (14). Thus, the VP model is broadly consistent with emerging physiological findings.…”
Section: B Asupporting
confidence: 66%
“…We assumed that neuronal variability had two sources (1,11,(35)(36)(37): the first resulted from the variations in the population rate r(t) mainly caused by transitions between silent and active network attractors, and the second arising from spiking stochasticity existent at constant rate. Neurons fired statistically identical Poisson spike trains with rate r(t).…”
Section: Methodsmentioning
confidence: 99%
“…To understand the mechanisms underlying correlations and their relation with silence density, we analyzed a model with two sources of neuronal variability: the first reflecting variations in the firing rate r, and the second reflecting the spiking stochasticity existent at constant rate (1,11,(35)(36)(37). Under this assumption, spike count correlations could be explained, at least in part, if the rate variability was correlated across neurons (35,37).…”
Section: Computational Rate Model Reproduces ρ-S Relation Across Brainmentioning
confidence: 99%
“…Previous studies reported increasing trial-to-trial variability in neural activities leading up to a voluntary movement onset (Steinmetz and Moore, 2010;Churchland et al, 2011), whereas stimulus onset quenches neural variability (Steinmetz and Moore, 2010;Churchland et al, 2010;Litwin-Kumar and Doiron, 2012). As the EODR reflects the neural activity associated with sensory sampling, we examined how EODR activity varied between trials during spontaneous and evoked transitions as a proxy for the variation in neural activity.…”
Section: Preparatory Increase In the Sensory Sampling Variabilitymentioning
confidence: 99%